Acute effect of foot orthotics on drag area and perceived comfort in cyclists affected by an anatomic asymmetry in time trial position - Bouillod, A.; Retali, M.; Soto-Romero, G.; Brunet, E.; Frémeaux, M.; Cassirame, J.; Maillot, J.; Grappe, F. (Journal of Science and Cycling, 2020)
The aim of this study was to analyse the acute effect of foot orthotics on drag area (ACd) and perceived comfort in cyclists affected by a lower limb length inequality (LLLI) in time trial (TT) position. Twenty-nine well-trained cyclists performed two discontinuous incremental exercises (before and after orthopaedic correction) using their personal TT bicycle and equipment on a 250-m indoor velodrome. The ACd was unchanged in both the test group (TG) ( 0.5%, p = 0.707) and the control group (CG) (-1.4%, p = 0.276), whereas the perceived comfort was improved in the TG (+6.2%, p = 0.002) and stabilised in the CG (+0.7%, p = 0.546), after the fitting of the foot orthotics. Pelvis movements were decreased (small effect size) in the TG (-6.2%, p = 0.093, ES = 0.251), whereas they were increased (small effect size) in the CG (+5.2%, p = 0.159, ES = 0.215). TT position was slightly improved by compensating for a LLLI, as the ACd was stabilised and the level of comfort was improved. Thus, cyclists affected by a LLLI are recommended to compensate with foot orthotics in order to improve their level of comfort and consequently their performance in TT position.